Pengaruh Struktur Kepemilikan Terhadap Penghindaran Pajak dengan CSR sebagai Variabel Mediasi - Intan Ramadhani; Yanis Ulul Az'mi (InFestasi, 2024)
Tax avoidance is a legal method for minimizing company taxes by exploiting loopholes in the tax system. Ownership structure plays an important role in a company's tax avoidance decisions, because the level of ownership can give rise to differences in attitudes in a company's decision-making, including decisions regarding tax avoidance activities. This research aims to analyze the mediating effect of corporate social responsibility ownership structure on tax avoidance. This research sample includes manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used in this research was purposive sampling, so the sample used amounted to 249 data. Path analysis is used as an analysis method. This research shows that ownership structure encourages corporate social responsibility practices in companies. The research results show that corporate social responsibility can mediate the influence of ownership structure on tax avoidance. The research provides main implications regarding the important role of social responsibility for companies to minimize the potential for tax avoidance.